2020
DOI: 10.1159/000510922
|View full text |Cite
|
Sign up to set email alerts
|

Compulsive Health-Related Internet Use and Cyberchondria

Abstract: <b><i>Background:</i></b> Cyberchondria denotes excessive and repeated online health-related searches associated with an increase in health anxiety. Such searches persist in those with cyberchondria, despite the negative consequences, resembling a pattern of compulsive Internet use. <b><i>Objectives:</i></b> The aim of the present study was to assess compulsive health-related Internet use in relation to cyberchondria while controlling for related variables. <b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 68 publications
2
18
0
2
Order By: Relevance
“…Similarly, symptoms of anxiety, depression, and sleep disturbances were associated with PIU among the medical population in studies conducted in other countries (Capetillo-Ventura and Juárez-Treviño, 2015;Younes et al, 2016;Grover et al, 2019;Shadzi et al, 2020). Recent studies found that PIU correlates with sleep problems, depression, and anxiety in non-medical populations as well (de Vries and Nakamae, 2018;Khazaal et al, 2021).…”
Section: Discussionmentioning
confidence: 84%
“…Similarly, symptoms of anxiety, depression, and sleep disturbances were associated with PIU among the medical population in studies conducted in other countries (Capetillo-Ventura and Juárez-Treviño, 2015;Younes et al, 2016;Grover et al, 2019;Shadzi et al, 2020). Recent studies found that PIU correlates with sleep problems, depression, and anxiety in non-medical populations as well (de Vries and Nakamae, 2018;Khazaal et al, 2021).…”
Section: Discussionmentioning
confidence: 84%
“…Abdelsattar et al ( 2021 ) in their research on a sample group of Arab individuals, concluded that there is a positive relationship between the severity of cybercoderia and fear of COVID-19. In some studies, it has been concluded that addictions to smartphones, the internet and/or social media is associated with cyberchondria severity (Fergus & Spada, 2017 ; Ivanova, 2013 ; Ivanova & Karabeova, 2014 ; Khazaal et al 2020 ). Other studies have reported that individuals who experience intense anxiety and fear during pandemics engage in behaviors that make them safe (Gaygisiz et al, 2012 ; Main et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, sport is also associated to positive health outcomes and commonly considered as an efficient health prevention strategy. Therefore, one could wonder how excessive and compulsive exercising could be associated to other compulsive behaviors toward health, such as cyberchondria (i.e., excessive and repeated online health-related searches associated with health anxiety) [62].…”
Section: Discussionmentioning
confidence: 99%